Temperature independent fatigue-free behavior in sodium bismuth titanate-based lead-free ceramics. (15th March 2021) - Kong, Yuxia; Li, Xin; Li, Zhengxiang; Hao, Jigong
Abstract: In this work, excellent electrostrictive properties with a giant electrostrain of 0.46% and a large electrostriction coefficient of 0.028 m 4 /C 2 were achieved in Ni/Mn-modified (Bi0.5 Na0.5 )0.935 Ba0.065 TiO3 ceramics. For high-temperature performance, an interesting finding is that the temperature stability of electrostrain is strongly dependent on the applied electric field strengths, that is, the lower the electric field is, the higher the temperature stability will be. A model of the electric-field-induced phase transition was introduced to find the causes of the different stability behaviors at various electric field strengths. The Ni/Mn-modified sample exhibited a fatigue-free behavior that was insensitive to temperature, which can be related to the reversible field-induced ergodic relaxor-ferroelectric phase transition. In addition, the fine-grained microstructure of the ceramics could also provide a high resistance to field cycling and thus improve the fatigue resistance. The current materials show great potential for actuator applications that require good cycling reliability. Graphical abstract: In this work, we designed Ni/Mn-modified BNT-based ceramics with a large electrostrain. An interesting finding is that the temperature stability of electrostrain is strongly dependent on the applied electric field strengths, that is, the lower the electric field is, the higher the temperature stability will be. A model of the electric-field-induced phase transition was introduced to find the causes of the different stability behaviors at various electric field strengths. Moreover, the modified material exhibited a temperature independent fatigue-free behavior due to its fine-grained microstructure and the reversible field-induced ergodic relaxor-ferroelectric phase transition. Such behavior renders the material have great potential for actuator applications that require good cycling reliability Image, graphical abstract .